How Language Competence and Anxiety Shape EFL Participation: Speaking Up or Staying Silent? - Tahang, Heriyanti; Hastina, Sri; Ibrahim, Ibrahim; Herlinawati, Herlinawati; Asrifan, Andi (The Institute of Research and Community Service (LPPM) - Universitas Lancang Kuning, 2025)
This research investigated students' participation patterns and the factors affecting them in non-skill lessons in EFL (English as a Foreign Language) lessons with discussion as the primary method. Understanding engagement in these lessons is crucial for enhancing classroom interaction and achieving learning objectives. A descriptive qualitative approach was employed, involving 34 fifth-semester students from an English Language Education program. Data were collected through twelve non-participation observations (examining participants' behaviour in different sessions based on Liu's theory) and a Guttmann scale questionnaire adapted from Hamouda assessing factors affecting participation. The observations revealed four participation patterns: marginal interaction (38.2%), silence observation (35.3%), conditional participation (18.7%), and full integration (11.8%). While the questionnaire identified language competence and psychological factors as two key factors influencing participation. The findings showed that students in full integration and conditional participation categories (30.5%) engaged more when having confidence in their vocabulary. In comparison, students in marginal interaction and silence observation categories (73.5%) were more hesitant due to concerns with grammar and a fear of making mistakes. Psychologically, full integration students were concerned with adverse outcomes, whereas those in marginal and silent categories struggled with shyness, low confidence, and uncertainty. This study contributes by exploring how linguistic and psychological factors shape participation, specifically in non-skill lessons in EFL. The findings suggest that teachers should foster supportive, low-pressure environments to encourage student engagement in addition to improving language competence. Curriculum designers can focus on activities that promote vocabulary development and confidence-building exercises to enhance participation in such lessons.